2003
DOI: 10.1046/j.1439-0523.2003.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of moniliformin produced by Fusarium species in grains of transgenic Bt maize hybrids compared to their isogenic counterparts and commercial varieties under European corn borer pressure

Abstract: The European corn borer (ECB), Ostrinia nubilalis Hb., is a major pest of maize in Central Europe and is suspected to promote infection of maize with Fusarium species. The objectives of this study were to (1) determine moniliformin (MON) concentration in early maturing European Bt maize hybrids, their isogenic counterparts, commercial cultivars and experimental hybrids, (2) evaluate the association between MON concentration and ECB resistance and (3) correlate MON concentration with concentrations of other myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The collected data confirm an important link between MON contamination and ECB activity performing to the damage of maize ears, which was also observed also by Papst et al (Papst et al 2005) in Germany, in a comparative study on Bt maize and its isogenic counterparts. Moreover, Papst et al (Papst et al 2005) and Magg et al (Magg et al 2003) reported a significant correlation between the percentage of ECB damaged ears and the MON concentration in the kernel: the MON content in ears manually infested with ECB larvae was times higher than the control, which has been protected through an insecticide application.…”
Section: Naturally Contaminated Samplesmentioning
confidence: 99%
“…The collected data confirm an important link between MON contamination and ECB activity performing to the damage of maize ears, which was also observed also by Papst et al (Papst et al 2005) in Germany, in a comparative study on Bt maize and its isogenic counterparts. Moreover, Papst et al (Papst et al 2005) and Magg et al (Magg et al 2003) reported a significant correlation between the percentage of ECB damaged ears and the MON concentration in the kernel: the MON content in ears manually infested with ECB larvae was times higher than the control, which has been protected through an insecticide application.…”
Section: Naturally Contaminated Samplesmentioning
confidence: 99%
“…Moreover, Papst et al (2005) and Magg et al (2003), in comparative studies on Bt maize and its isogenic counterparts conducted in Central Europe, have also reported a significant correlation between the percentage of ECB damaged ears and the MON concentration. Unfortunately, at the moment, no data are available on the effect of ECB on MON contents in warmer maize cultivation areas, where the pressure and damage caused to ears and kernels by this insect are higher.…”
Section: Introductionmentioning
confidence: 96%
“…In the infested plots, the MON concentrations were 153.5, 336.7 and 266.1 µg/kg for the transgenic, isogenic and commercial hybrids, respectively. In contrast, in the protected plots, the MON concentrations were 49.1, 99.3 and 42.9 µg/kg for the transgenic, isogenic and commercial hybrids, respectively (Magg et al, 2003).…”
Section: Contamination With Other Mycotoxins In Bt and Non-bt Maizementioning
confidence: 83%